The effect of chrysin–curcumin-loaded nanofibres on the wound-healing process in male rats - Zoheyr Mohammadi; Mohsen Sharif Zak; Hasan Majdi; Ebrahim Mostafavi; Meisam Barati; Hamid Lotfimehr; Kambiz Ghaseminasab; Hamidreza Pazoki-Toroudi; Thomas J. Webster; Abolfazl Akbarzadeh (Artificial Cells, Nanomedicine, and Biotechnology)
Aim The aim of the present study was to produce chrysin–curcumin-loaded PCL-PEG nanofibres by an electrospinning technique and to evaluate the biological activity of the chrysin–curcumin-loaded PCL-PEG fibres for wound healing and its related genes using in vivo methods.Materials and methods The electrospinning method was carried out for the preparation of the chrysin, curcumin and chrysin–curcumin-loaded PCL-PEG nanofibres with different concentrations. FTIR and SEM were performed to characterize the chemical structures and morphology of the nanofibres. In vitro drug release, as well as in vivo wound-healing studies were investigated in male rats. The expressions of genes related to the wound-healing process were also evaluated by real-time PCR.Results Our study showed that the chrysin–curcumin-loaded nanofibres have anti-inflammatory properties in several stages of the wound-healing process by affecting the IL-6, MMP-2, TIMP-1, TIMP-2 and iNOS gene expression. Our results demonstrated that the effect of the chrysin-loaded nanofibre, the curcumin-loaded nanofibre and the chrysin–curcumin-loaded nanofibre in the wound-healing process is dose dependent and in accordance with the obtained results in that it might affect the inflammation phase more than the other stages of the wound-healing process.Conclusion We have introduced chrysin–curcumin-loaded PCL-PEG nanofibres as a novel compound for shortening the duration of the wound-healing process.